2010
DOI: 10.1038/embor.2010.61
|View full text |Cite
|
Sign up to set email alerts
|

SOX5 controls cell cycle progression in neural progenitors by interfering with the WNT–β‐catenin pathway

Abstract: Genes of the SOX family of high-mobility group transcription factors are essential during nervous system development. In this study, we show that SOX5 is expressed by neural progenitors in the chick spinal cord and is turned off as differentiation proceeds. The overexpression of SOX5 in neural progenitors causes premature cell cycle exit and prevents terminal differentiation. Conversely, knocking down SOX5 protein extends the proliferative period of neural progenitors and causes marked cell death in a dorsal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 19 publications
3
73
0
1
Order By: Relevance
“…4C and data not shown). In light of the evidence that Sox5 regulated p27 protein levels via the Akt or β-catenin pathway [18,31], we further examined the levels of phosphorylated and total Akt and β-catenin in transduced human multiple myeloma cells. We found that overexpression of either Sox5-BLM or L-Sox5 caused robust up-regulation of the total protein levels of β-catenin, but not Akt (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4C and data not shown). In light of the evidence that Sox5 regulated p27 protein levels via the Akt or β-catenin pathway [18,31], we further examined the levels of phosphorylated and total Akt and β-catenin in transduced human multiple myeloma cells. We found that overexpression of either Sox5-BLM or L-Sox5 caused robust up-regulation of the total protein levels of β-catenin, but not Akt (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Sox5 suppresses PDGFB-induced glioma development in Ink4a -/- mice [31]. Interestingly, increased levels of p27 upon Sox5 expression were also observed in PDGFB-induced glioma of Ink4a -/- mice and in chicken developing neurons [18,31]. However, overexpression of Sox5 results in a decrease in the levels of the dephosphorylated active form of β-catenin in chicken developing neurons [18], but an increase in the levels of β-catenin in human multiple myeloma cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the maintenance of proliferation does not always prevent cells from differentiating (Dyer and Cepko, 2000). Sox5 causes premature cell cycle exit in neural progenitor cells in the chick spinal cord, but also prevents differentiation (Martinez-Morales et al, 2010). Although we have shown that Sox17 regulates the promoters of myelin genes (Sohn et al, 2006), other components of the pathway e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the long isoform of Sox5 (L-Sox5) is expressed in multiple tissues, including the cartilage, heart, brain, kidney, lung, and skeletal muscle [29,31,32]. L-Sox5 has been shown to play important roles in regulating processes of embryonic development and cell fate determination, including chondrogenesis [33], neural crest development [34,35], oligodendrogenesis [36], lung development [32], and generation of cortical neurons [27]. Sox5 proteins achieve these developmental roles by modulating cell proliferation, survival, differentiation, or terminal maturation in different cell lineages [24].…”
Section: Introductionmentioning
confidence: 94%